City of Refuge : Separatists and Utopian Town Planning - Lewis, Michael J., 1957- (Book collections on Project MUSE., 2016)
"The vision of Utopia obsessed the nineteenth-century mind, shaping art, literature, and especially town planning. In City of Refuge, Michael Lewis takes readers across centuries and continents to show how Utopian town planning produced a distinctive type of settlement characterized by its square plan, collective ownership of properties, and communal dormitories. Some of these settlements were sanctuaries from religious persecution, like those of the German Rappites, French Huguenots, and American Shakers, while others were sanctuaries from the Industrial Revolution, like those imagined by Charles Fourier, Robert Owen, and other Utopian visionaries. Because of their differences in ideology and theology, these settlements have traditionally been viewed separately, but Lewis shows how they are part of a continuous intellectual tradition that stretches from the early Protestant Reformation into modern times. Through close readings of architectural plans and archival documents, many previously unpublished, he shows the network of connections between these seemingly disparate Utopian settlements--including even such well-known town plans as those of New Haven and Philadelphia. The most remarkable aspect of the city of refuge is the inventive way it fused its eclectic sources, ranging from the encampments of the ancient Israelites as described in the Bible to the detailed social program of Thomas More's Utopia to modern thought about education, science, and technology. Delving into the historical evolution and antecedents of Utopian towns and cities, City of Refuge alters notions of what a Utopian community can and should be"--Provided by publisher.